Effects of mounding on soil properties, root development, and physiological responses of Ganoderma boninense-infected and uninfected oil palms - Muhdan Syarovy; Sumaryanto Sumaryanto; Syarul Nugroho; Valdi Muhamad Rafiansyah Siregar; Eka Wijayanti (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2025)
Basal stem rot (BSR), caused by Ganoderma boninense, is a major disease in oil palm plantations, leading to significant losses. Currently, there is no fully effective method to control this disease. This study evaluated the effects of mounding techniques on root development in both Ganoderma-infected and uninfected oil palms over 8 months. The research was conducted across six plantations in North Sumatra, where root biomass was measured by uncovering a quarter of the mounded area and analyzing the soil's physical and chemical properties. The results showed that, although most soil properties were comparable, cation exchange capacity (CEC) and magnesium (Mg) levels were higher in uninfected palms. Root growth increased in both infected and uninfected palms from three to eight months after mounding, but by the seventh and eighth months, the root biomass in infected palms was lower compared to uninfected palms. Infected palms primarily showed the growth of primary-like roots, whereas uninfected palms exhibited more extensive tertiary and quaternary roots. The study concluded that while mounding stimulates root development, Ganoderma infection limits this growth. These findings have important implications for improving disease management strategies in oil palm plantations.